2022
DOI: 10.1136/spcare-2021-003511
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life and immediate postdeath acute hospital interventions: scoping review

Abstract: BackgroundHospital remains the most common place of death in the UK, but there are ongoing concerns about the quality of end-of-life care provision in this setting. Evaluation of interventions in the last days of life or after a bereavement is methodologically and ethically challenging.AimThe aim was to describe interventions at the very end of life and in the immediate bereavement period in acute hospitals, with a particular focus on how these are evaluated.MethodA scoping review was conducted. Studies were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…32 Participants at both the Stage 1 and 2 Trusts reported the embedding of memory-making activities; these types of interventions were found to be valued by bereaved families in previous qualitative research. 19 The SWAN model of care improved the overall attention to end-of-life and bereavement care, as demonstrated through the qualitative findings as well as routinely collected data such as end-of-life care plans as well as timely mortuary transfer, which then enabled potential tissue donation, as desired by families, in accordance with their loved ones' preferences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Participants at both the Stage 1 and 2 Trusts reported the embedding of memory-making activities; these types of interventions were found to be valued by bereaved families in previous qualitative research. 19 The SWAN model of care improved the overall attention to end-of-life and bereavement care, as demonstrated through the qualitative findings as well as routinely collected data such as end-of-life care plans as well as timely mortuary transfer, which then enabled potential tissue donation, as desired by families, in accordance with their loved ones' preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations of end-of-life and bereavement care are scarce and are predominantly survey-based 19 ; in contrast this evaluation, using a realistic approach, included qualitative interview data as well as analyses of routinely collected qualitative and quantitative data. The use of a mixed method realist evaluation captured the nuances of what it is about the SWAN model that brings about change and the context (‘for whom’ and ‘in what circumstances’) SWAN works.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions at the EoL are underinvestigated due, in part, to the considerable methodological and ethical challenges, meaning that patient experiences often go unheard—this research therefore fills an important gap in literature. 10 This article draws on a research project which explored the national implementation of EoL policy, in which a wide range of stakeholders were interviewed to explore alignment of policy priorities in each group, and the broader study is reported elsewhere. 6 11 The paper focusses on the voice of older people aged 75+ years, identified by clinicians as being at the EoL, and their carers, to reflect on how to align current system pressures with patient wishes.…”
Section: Objectivesmentioning
confidence: 99%